Cosmetics, dermocosmetics and cosmeceuticals in aesthetic medicine: what we have never asked, and why it matters. A clinical perspective - Georgescu, Cristina; Bartoletti, Emanuele (Aesthetic Medicine, 2026)
Introduction: Dermocosmetics are widely used in aesthetic and dermatologic practices; however, they remain one of the most conceptually misunderstood tools available to clinicians. Terms such as “cosmetic,” “dermocosmetic,” and “cosmeceutical” are frequently employed as if they reflected distinct regulatory or scientific categories, whereas, in practice, they represent cultural, methodological, and clinical gradients rather than legal definitions.Objectives: This perspective aims to clarify these conceptual boundaries and examine the scientific elements that distinguish dermocosmetics from standard cosmetics, without conferring upon them a therapeutic role.Methods: By integrating regulatory context, formulation science, methodological rigor, and clinical relevance, this paper provides an evidence-informed framework for evaluating dermocosmetics in clinical practice.Results: This framework highlights the differences between dermocosmetics and standard cosmetics, offering clinicians a structured approach to interpret their use beyond marketing terminology.Conclusions: The goal is not to elevate dermocosmetics as a “superior” product class, but to provide clinicians with the knowledge needed to guide patients responsibly in an area where marketing vocabulary often obscures scientific meaning.